2018
DOI: 10.1111/jan.13833
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of people living with disorders of sex development and sex reassignment: Meta‐ethnography of qualitative studies

Abstract: Disorders of sex development affect the quality of life of people living with these disorders. Nurses are tasked with providing holistic care for people with disorders of sex development in order to improve their quality of lives. As such, there is a need to explore the experiences of nurses in the management of disorders of sex development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(209 reference statements)
1
5
0
Order By: Relevance
“…As psychologists, we understand that the ability to talk with others and to share information about oneself can be fundamental to psychosocial well-being (Roen 2019) and that development happens in an ecological context (Schweizer et al 2017). Our findings resonate with others by showing that talking to others about variations in sex characteristics is framed by fear of rejection (e.g., Jones et al 2016, Alderson, Madill, and Balen 2004, Sani et al 2019, Guntram and Zeiler 2016, limited social understanding of intersex characteristics (Enzendorfer and Haller 2020, Breu 2009, Jones et al 2016, The European Union Fundamental Rights Agency 2020, Liao 2003 and problematic understandings of gendered embodiment as binary (Brömdal et al 2017, Guntram andZeiler 2016). Some young people want to talk about their variation because they want to connect with others, derive support and talk about their future, including honest talk with partners (see also Ernst et al 2016, Liao 2003.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As psychologists, we understand that the ability to talk with others and to share information about oneself can be fundamental to psychosocial well-being (Roen 2019) and that development happens in an ecological context (Schweizer et al 2017). Our findings resonate with others by showing that talking to others about variations in sex characteristics is framed by fear of rejection (e.g., Jones et al 2016, Alderson, Madill, and Balen 2004, Sani et al 2019, Guntram and Zeiler 2016, limited social understanding of intersex characteristics (Enzendorfer and Haller 2020, Breu 2009, Jones et al 2016, The European Union Fundamental Rights Agency 2020, Liao 2003 and problematic understandings of gendered embodiment as binary (Brömdal et al 2017, Guntram andZeiler 2016). Some young people want to talk about their variation because they want to connect with others, derive support and talk about their future, including honest talk with partners (see also Ernst et al 2016, Liao 2003.…”
Section: Discussionsupporting
confidence: 72%
“…The research described in this article engages the dynamic between what is talkable and what is not talkable in relation to sex characteristics. We understand that many people with variations in sex characteristics find communicating with others challenging, especially when it comes to talking to peers, such as friends and classmates and (potential) partners (Jones et al 2016, Sani et al 2019, Schweizer et al 2017, Frank 2018, Liao et al 2010, Engberg et al 2016, Carroll et al 2020. Some people fear being devalued (Alderson, Madill, and Balen 2004) or rejected (Ernst et al 2016, Frank 2018, Guntram and Zeiler 2016 and some have experienced negative or unhelpful responses from others (Jones et al 2016, Ernst et al 2016, Malouf et al 2010.…”
Section: Making Things 'Talkable': Young People's (Communication) Needsmentioning
confidence: 99%
“…Some quantitative studies involving individuals with different DSD reported the participants to exhibit overall satisfaction with their sexual health (Engberg et al, 2022 ; Schönbucher et al, 2008 ), whereas other quantitative studies found that DSD had a negative impact on participants’ emotional and sexual well-being (Liao et al, 2011 van de Grift et al, 2022 ). A meta-ethnography of 16 qualitative studies concerning DSD suggested sexual health to be negatively related to DSD and, consequently, quality of life (Sani et al, 2019 ). The medical consequences of DSD (type and severity), psychological experiences of treatment (e.g., distress, anxiety), and reactions from others (e.g., stigma) have all been found to have a negative influence on sexual health (Meyer-Bahlburg et al, 2018 ; Wisniewski et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…While some people find strategies to navigate these challenges in everyday life on their own, others find community support and professional psychosocial input useful. Support can be provided by significant others, support or activist groups, or healthcare providers, including psychosocial professionals (Sani et al, 2019).…”
Section: Schützmann Et Al's Literature Review Focuses On Psychologica...mentioning
confidence: 99%